Etika Menjaga Lisan dalam Hadis dan Fenomena Cancel Culture di Media Sosial: Analisis Emosi Publik dalam Ruang Publik Digital - Laela Sari Agustina; Uswatun Hasanah; Nuchalidin Nuchalidin (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
The phenomenon of cancel culture has become one of the major dynamics in contemporary digital communication, characterized by collective forms of social punishment carried out through social media platforms. Within the digital public sphere shaped by algorithmic virality, public emotional responses often develop rapidly without adequate processes of information verification. This condition frequently triggers practices of online shaming, narrative distortion, and reputational damage toward individuals. This study aims to analyze the relevance of the Prophet’s hadith concerning the ethics of guarding one’s speech in responding to the phenomenon of cancel culture on social media. The research employs a qualitative method based on library research with a thematic-contextual approach to hadiths related to communication ethics, self-restraint, and the principle of amar ma‘ruf nahi munkar. The findings show that the teachings of Prophet Muhammad, such as the command to speak good or remain silent and the prohibition against spreading information without verification, possess strong relevance to contemporary challenges in digital communication. These principles can be understood as an ethical communication framework emphasizing information verification (tabayyun), the regulation of public emotion, and the protection of human dignity (hifẓ al-‘ird). Therefore, hadith-based communication ethics may serve as a normative framework for developing a more ethical, fair, and responsible culture of digital communication within the dynamics of the digital public sphere.